Film-induced tourism : The movie as a tool to attract visitors - Babinets, Ilona; Janeček, Petr; Pichlík, Lukáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This Bachelor thesis focuses on a phenomenon called film-induced tourism whereby individuals are inspired to visit featured destinations showcased in films and television shows. Data for this study were gathered from scientific articles and journals. The theoretical framework includes the definition of film tourism, its main concepts, impacts and the importance of its presence in contemporary media, backed up with examples of successful movie scenes. The empirical part lies in conducting a quantitative survey, where participants expressed their opinions and experiences about film-induced tourism along with travel preferences. The participants of the questionnaire were the general public of different ages and nationalities, which led to understanding people’s preferences, expectations and experiences connected with film-induced tourism and their possible desire to visit any of the movie locations. The analysis of the movie and travel preferences of respondents allowed the creation of a travel itinerary based on their choices. The main outcome of this Bachelor thesis is the finding that the power of film-induced tourism is significant in defining a destination image as it is one of the growing fields and has great potential in the future, contributing to the existing knowledge of the concept.
Vedoucí práce: Petr Janeček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: cestovní ruch [obor bakal. práce]; bakalářské práce; bachelor's theses